Ratio of Legal Systems (cont.) The evolution of Ideas about the Content of the “Traditional” Doctrines on the Ratio of Legal Systems (Summary) - B. I. Nefedov (Московский журнал международного права, 2013)
The emergence in the late 50’s and early 60’s of the previous century of the new practice of the adoption by the USSR so-called “self-executing” treaties and of new definitions of the Soviet legislation about the superiority of the International treaties over national law, required critical rethinking of prevailing perceptions in our country of the “traditional” doctrine of the ratio of international and domestic law. Forms of interaction of legal systems in the regulation of social relations, in particular in our country, were much more diverse than previously thought to be. The realization of what had happened did not come immediately, and not to everyone. There was a group of Soviet scientists, who tried to “squeeze” a new situation within the framework of the Soviet concept of the relation of legal systems, and put forward a theory of “transformation” of international treaties into domestic law rules, unreasonably blaming those, who thought it possible the direct application of international law as a regulator of social relations in our country in monism.At the same time the number of “new” theories of the ratio of international and domestic law dramatically increases, both in Russia and abroad. In fact, almost all of them are not theories of relationships within the legal systems of law as such, but a reflection of an existing real or formally proclaimed by the private practice of different countries to implement the provisions of international law.